The bees of the tribe Anthophorini Dahlbom, 1835 (Hymenoptera: Apoidea: Apidae) of Nakhchichivan Autonomous Republic of the Azerbaijan - Maharramov, M. M.; Aliyev, Kh. A.; Bayramov, A. B. (Acta Biologica Sibirica, 2018)
In the entomofauna of the Nakhchivan Autonomous Republic, 37 species of true bees belonging to 3 genera of the tribe Anthophorini, found at different times within the area of the autonomous republic is presented. The genus Amegilla is represented 3 subgenus (Amegilla, Micramegilla, Zebramegilla) and 7 species, the genus Anthophora 7 subgenus (Anthophora, Caranthophora, Dasymegilla, Heliophila, Lophanthophora, Melea, Paramegilla, Petalosternon, Pyganthophora) and 28 species, and the genus Hapropoda 2 species. Anthophora bimaculata (Panzer, 1798), A. richaensis Alfken, 1938, A. gracilipes (Morawitz, 1872), A. harmalae Morawitz, 1878, A. meridionalis Fedtschenko, 1875 and A. podagra Lepeletier, 1841 are newly recorded from Nakhchivan AR. The habitat landscapes of those species, biotopes and their feeding sources, entomophilous plants, are identified. Species of tribe Anthophorini feed on flowers of plant species of 19 families of the flora of the autonomous republic. A great preference is given to the flowers of the plants of the families Asteraceae, Fabaceae and Lamiaceae.